(untitled) (LACCEI, 2024)
Defective urban planning, deficient drainage systems, basin hydrological studies in addition to traditional pavements, which prevent the penetrability of water and lead to its wastage and inadequate conduction, demonstrated that the city of Trujillo is not in the right conditions, to face problems derived from precipitation. That is why, under an applied, quantitative, experimental quasi-experimental and explanatory investigation, we sought to analyze the influence of permeable pavement in the urban environment as an alternative to mitigate meteorological impacts that affect the town in 2022. The technique of Information gathering was observation and used the observation guide as an instrument Likewise, the data collection from and information tables on the samples that were the cylindrical and prismatic specimens of porous concrete with a percentage of voids at 13, 15 and 17 were used. As a result of the process, it was found that the rigid pavement proposal permeable to improve human coexistence with the road infrastructure that the city of Trujillo has, offering a porous configuration that reduces water runoff, the common of vehicle, safety for pedestrians, generating control in rains and its application, likewise, contributes with the natural environment generating the conservation of the water cycle and brings Trujillo closer to being a sustainable city.